Missed opportunities for sexually transmitted infections testing for HIV pre‐exposure prophylaxis users: a systematic review. Issue 2 (18th February 2021) - Ong, Jason J; Fu, Hongyun; Baggaley, Rachel C; Wi, Teodora E; Tucker, Joseph D; Smith, M Kumi; Rafael, Sabrina; Falconer, Jane; Terris‐Prestholt, Fern; Mameletzis, Ioannis; Mayaud, Phillipe
Abstract: Introduction: Given the synergistic relationship between HIV and sexually transmitted infections (STI), the integration of services has the potential to reduce the incidence of both HIV and STIs. We explored the extent to which STI testing has been offered within HIV pre‐exposure prophylaxis (PrEP) programmes worldwide. Methods: We conducted a systematic review of PrEP programmes implementing STI testing services in nine databases. We approached PrEP implementers for additional unpublished data and implementation details. Descriptive statistics were used to present the characteristics of STI testing within PrEP programmes. Content analysis of the input from PrEP implementers was conducted to summarize the barriers to and facilitators of STI testing. Results: Of 9, 161 citations, 91 studies conducted in 32 countries were included: 69% from high‐income countries (HICs) and 64% from programmes targeting men who have sex with men (MSM) and transgender women (TGW) only. The majority of programmes (70%, 64/91) conducted STI testing before the initiation of PrEP. The most common STIs tested were gonorrhoea (86%, 78/91), chlamydia (84%, 76/91) and syphilis (84%, 76/91). The majority provided STI testing at three‐month intervals (70%, 53/76, for syphilis; 70% 53/78, for chlamydia; 68%, 53/78, for gonorrhoea). Relative to low‐ and middle‐income countries (LMICs), a higher proportion of PrEP programmes in HICs offered testing for gonorrhoea (92% vs. 71%, p  < 0.05), chlamydia (92% vs. 64%, p  < 0.01), syphilis (87% vs. 75%, p  < 0.05), hepatitis A (18% vs. 4%, p  < 0.05) and hepatitis C (43% vs. 21%, p  < 0.05); offered testing for a higher number of STIs (mean 3.75 vs. 3.04, p  < 0.05); and offered triple (throat, genital/urine and anorectal) anatomical site screening (54% vs. 18%, p  < 0.001). Common implementation challenges included costs, access to STI diagnostics, programme logistics of integrating STI testing into PrEP delivery models and lack of capacity building for staff involved in PrEP provision. Conclusions: Significant gaps and challenges remain in the provision of STI testing services within HIV PrEP programmes. We recommend more active integration of STI testing and management into PrEP programmes, supported by standardized practice guidelines, staff capacity building training and adequate funding. This could lead to improved sexual health and HIV outcomes in key populations.